A Key Distribution Scheme for WSN Based on Hash Chains and Deployment Knowledge. (1st July 2015) - You, Lin; Yuan, Younan; Yu, Wangke; Wang, Qiuhua
Based on the deployment knowledge and the irreversibility of some hash chains, a novel pairwise key distribution scheme (DKH-KD) for wireless sensor networks is proposed. In DKH-KD scheme, before the nodes in the network are deployed, the offline server constructs a number of hash chains and uses the values from a pair of reverse hash chains to establish their pairwise keys among the nodes in the same region, while, among the neighbor nodes in the different regions, some pairs of the hash chains based on the deployment knowledge are employed to establish the pairwise keys. These procedures make the attackers hard to break the network and ensure that the probability of the pairwise key establishment is close to 1. Compared with the Dai scheme and the q -composite's scheme, our analyses show that DKH-KD scheme can improve the probability of the pairwise key establishment and the invulnerability more efficiently.